2019
DOI: 10.1007/s13340-019-00390-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of cancer in Japanese patients with type 2 diabetes: the Fukuoka Diabetes Registry

Abstract: Background Although the association between type 2 diabetes and cancer has been reported, few epidemiological studies have been conducted in Japanese patients whose leading cause of death is cancer. We prospectively studied the incidence of site-specific cancer, risk factors for developing cancer, cancer death, and survival in Japanese patients with type 2 diabetes. Methods We followed 4923 participants (mean age, 65 years) with type 2 diabetes attending an outpatient diabetes clinic for a median of 5.3 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The potential mechanisms underlying the link between T2DM and cancer include hyperglycemia, insulin resistance, high insulin levels and increased insulin-like growth factor I (IGF-1) levels, etc ( 29 ). Smoking, male gender and low-density lipoprotein cholesterol (LDL-C)<100mg/dl were found to be risk factors for diabetic patients to develop cancer, while body mass index (BMI), alcohol consumption and HbA1C levels were not associated with cancer occurrence in diabetic population ( 30 ). A prospective case-control study in Korea showed that higher blood glucose levels, lower high-density lipoprotein cholesterol (HDL-C) and homeostasis model assessment of insulin resistance (HOMA-IR) levels were associated with the risk of early stage gastric cancer ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms underlying the link between T2DM and cancer include hyperglycemia, insulin resistance, high insulin levels and increased insulin-like growth factor I (IGF-1) levels, etc ( 29 ). Smoking, male gender and low-density lipoprotein cholesterol (LDL-C)<100mg/dl were found to be risk factors for diabetic patients to develop cancer, while body mass index (BMI), alcohol consumption and HbA1C levels were not associated with cancer occurrence in diabetic population ( 30 ). A prospective case-control study in Korea showed that higher blood glucose levels, lower high-density lipoprotein cholesterol (HDL-C) and homeostasis model assessment of insulin resistance (HOMA-IR) levels were associated with the risk of early stage gastric cancer ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms underlying the link between T2DM and cancer include hyperglycemia, insulin resistance, high insulin levels and increased insulin-like growth factor I (IGF-1) levels, etc (29). Smoking, male gender and low-density lipoprotein cholesterol (LDL-C)<100mg/dl were found to be risk factors for diabetic patients to develop cancer, while body mass index (BMI), alcohol consumption and HbA1C levels were not associated with cancer occurrence in diabetic population (30). A prospective casecontrol study in Korea showed that higher blood glucose levels, lower high-density lipoprotein cholesterol (HDL-C) and homeostasis model assessment of insulin resistance (HOMA-IR) levels were associated with the risk of early stage gastric cancer (31).…”
Section: The Association Between T2dm With Gastric and Colorectal Cancermentioning
confidence: 99%
“…The potential mechanisms underlying the link between T2DM and cancer include hyperglycemia, insulin resistance, high insulin levels and increased insulin-like growth factor I (IGF-1) levels, etc (29). Smoking, male gender and low-density lipoprotein cholesterol (LDL-C)<100mg/dl were found to be risk factors for diabetic patients to develop cancer, while body mass index (BMI), alcohol consumption and HbA1C levels were not associated with cancer occurrence in diabetic population (30). A prospective casecontrol study in Korea showed that higher blood glucose levels, lower high-density lipoprotein cholesterol (HDL-C) and homeostasis model assessment of insulin resistance (HOMA-IR) levels were associated with the risk of early stage gastric cancer (31).…”
Section: The Association Between T2dm With Gastric and Colorectal Cancermentioning
confidence: 99%